Between Franks and Butler: British intelligence lessons from the Gulf War - Kettle, Louise (Taylor & Francis, 2016)
Lessons for the intelligence community were publicly identified in a 1983 report by Lord Franks and 2004 report by Lord Butler. However, little is known of the lessons learned during the twenty years between the two. This article draws upon two newly released, previously classified, documents which examine British intelligence lessons from the 1990-1991 Gulf War. It provides a previously untold account of the crisis, exclusively from a British intelligence perspective, and presents new evidence that intersects across many intelligence debates. This article also challenges whether identified lessons remained learned and begins to question the wider learning process within the intelligence community.